Political masks. Demonstrating visualities: from the disappeared during dictatorship to institutional violence in democracy. [DOI:10.37785/nw.v5n1.a5] - Di Filippo, Marilé; Cristiá, Moira (Nawi, 2021)
This article studies the use of masks in political demonstrations from the eighties to the present. In order to reflect on specific uses in different historical contexts, it analyzes masks’ physiognomic characteristics, their incorporation in each repertoire of protest, as well as its various symbolic aspirations. With this purpose, this paper explores a series of experiences related to the denunciation of forced disappearance during the dictatorships of the Southern Cone and in some cases of institutional violence in democracy in recent Argentina. It shows that while neutral masks were used in the former, individualized masks with the victims' faces were favored in the latter, composing various visual and performative interventions. Its differential use seems to correspond to particularities associated with the life and death of the victims at the same time that it generates different types of symbolic links between victims and the protesting body.